PEMIKIRAN POSMODERNISME DAN PANDANGANNYA TERHADAP PENDIDIKAN (Studi Kritis Atas Kurikulum Pendidikan Tinggi Indonesia) - M. Fajru Sidqi; Inayatul Ulya (LPPM Universitas Pekalongan, 2019)
Non schlae set vittae discinnus, this is a latin idiomatic to clear the purpose of educational purposes; we learn for not for school but for life. This article is inspired by phenomena of modernity, all have pragmatics orientation and erode the essence and value of education. Indonesia clear that claim, all system in education is structurized by certain portion in relation with jobfield, outline of modernity creates new world order in false-structure and lead by developed nation. They now drive the direction of education, what should be done by higher education to their curriculum, and fullfilling industrial need is a must as priority in curriculum sector. Posmodernity – perspective tries to pass the standart of modernity by making way out for science ideality, these are never ended process to revitalize new concept in developing curriculum in Higher education. Deconstruction is one key theory to offer some solution in managing curriculum, then library research is used to analyze by comparing ideal world by expert as their opinion to real situation in Indonesian education especially on curriculum concept.